2013
DOI: 10.1194/jlr.r031278
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids: regulators of crosstalk between apoptosis and autophagy

Abstract: decades ago, pioneering work by Hannun et al. and Kolesnick et al. established the foundation for the bioactive nature of sphingolipids by demonstrating the inhibition of protein kinase C (PKC) by sphingosine and the stimulation of a ceramide-activated protein kinase in response to tumor necrosis factor (TNF)-␣ , respectively ( 1, 2 ). Sphingolipids have since been recognized as critical activators or inhibitors of various protein kinases and phosphatases, receptors, and ion transporters ( 3 ). Moreover, sphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
274
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(297 citation statements)
references
References 178 publications
6
274
1
1
Order By: Relevance
“…33,34 This discrepancy may be attributable to the complex and diverse interplays between autophagy and other mechanisms of cell death. 35 In our experimental setting, we found that the decrease in cell viability and the induction of apoptosis occurred together to the increase of autophagosome vesicles, as assessed by upregulation of apoptotic, i.e., cleaved caspase 7, and autophagic markers, i.e., cleaved LC3B. The regulatory pathways of autophagy and apoptosis share several molecules, among these PI3K/AKT/mTOR plays an important role in radiation-induced autophagy.…”
Section: Discussionmentioning
confidence: 66%
“…33,34 This discrepancy may be attributable to the complex and diverse interplays between autophagy and other mechanisms of cell death. 35 In our experimental setting, we found that the decrease in cell viability and the induction of apoptosis occurred together to the increase of autophagosome vesicles, as assessed by upregulation of apoptotic, i.e., cleaved caspase 7, and autophagic markers, i.e., cleaved LC3B. The regulatory pathways of autophagy and apoptosis share several molecules, among these PI3K/AKT/mTOR plays an important role in radiation-induced autophagy.…”
Section: Discussionmentioning
confidence: 66%
“…The mechanism of ceramide-induced cell death through apoptosis is well established (12), inducing apoptosis through extrinsic and intrinsic pathways (13). The extrinsic apoptosis pathway is often triggered by the activation of tumor necrosis factor receptors, whereas the intrinsic pathway is initiated by mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests a possible link between the role of lipids in the regulation of apoptosis and autophagy (10). Autophagy is an evolutionary conserved pathway controlling the quality and quantity of eukaryotic organelles and the cytoplasmic biomass.…”
Section: Significancementioning
confidence: 99%